De-mystifying Translation Introducing Translation to Non-translators - Bowker, Lynne (Taylor & Francis, 2023)
This textbook provides an accessible introduction to the field of translation for students of other disciplines and readers who are not translators. It provides students outside the translation profession with a greater awareness of, and appreciation for, what goes into translation. Providing readers with tools for their own personal translation-related needs, this book encourages an ethical approach to translation and offers an insight into translation as a possible career. This textbook covers foundational concepts; key figures, groups, and events; tools and resources for non-professional translation tasks; and the types of translation that non-translators are liable to encounter. Each chapter includes practical activities, annotated further reading, and summaries of key points suitable for use in classrooms, online teaching, or self-study. There is also a glossary of key terms. De-mystifying Translation: Introducing Translation to Non-translators is the ideal text for any non-specialist taking a course on translation and for anyone interested in learning more about the field of translation and translation studies. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons (CC-BY-NC-ND) 4.0 license.